Difficult Nasal Polyposis: Evolving Treatments and Remedies. (23rd August 2013) - Woodworth, Bradford A.; Reh, Douglas D.; Palmer, James N.; Gosepath, Jan
Abstract : Program Description: Chronic sinusitis with nasal polyposis has a detrimental impact on quality of life and may exacerbate co‐existing conditions such as asthma. This miniseminar will outline the latest theories on disease pathogenesis as well as promote rational medical and surgical strategies for severe nasal polyposis management. Treatments designed to decrease reliance on systemic steroids, including surgical methods and complementary medical therapeutics such as topical steroid irrigations, macrolides, and anti‐leukotrienes, will be discussed. A panel of international experts will provide the latest innovations in medical and surgical treatments through a case‐based approach of difficult patients and strategies for success illustrating these advancements. Educational Objectives: 1) Interpret current theories on the pathogenesis of nasal polyposis. 2) Recognize the newest medical and surgical treatments for difficult nasal polyposis, including cystic fibrosis. 3) Initiate additional therapeutic measures to appropriately care for patients with severe nasal polyposis.